Us and the Bottle Man - Price, Edith Ballinger, 1897-1997 (Salt Lake City, UT : Project Gutenberg, 2004)
"Us and the Bottle Man" by Edith Ballinger Price is a children's adventure novel written in the early 20th century. The story centers around siblings Jerry, Greg, and Chris Holford, who embark on imaginative escapades during their summertime picnics on the island of Wecanicut. The children$1 (Bs childhood whims lead them to write a playful message in a bottle, which ultimately brings unexpected correspondence from a mysterious figure they call the "Bottle Man," setting the stage for unique adventures and growing friendship. The opening of the book introduces us to the three main characters and their setting, highlighting their playful schemes during a picnic. The siblings creatively compose a letter that reflects their excitement for adventure, which they toss into the sea in hopes of it being discovered. Their light-hearted activities, including pretending to be pirates and finding a mysterious "Sea Monster," capture the essence of childhood imagination. As they explore both their immediate surroundings and the boundless possibilities of the adventures they can dream up, readers are drawn into their vibrant world marked by camaraderie and curiosity. (This is an automatically generated summary.)s
Release date is 2004-06-01
E-text prepared by Thaadd, Susan Lucy, and Project Gutenberg Distributed Proofreaders
Keywords: Siblings -- Juvenile fiction; Seashore -- Juvenile fiction; New England -- Juvenile fiction; World War, 1914-1918 -- United States -- Juvenile fiction